The potential of liposome–encapsulated ciprofloxacin as a tularemia therapy - Hamblin, Karleigh A.; Wong, Jonathan P.; Blanchard, James D.; Atkins, Helen S. (Frontiers in Cellular and Infection Microbiology, 2014)
Liposome-encapsulation has been suggested as method to improve the efficacy of ciprofloxacin against the intracellular pathogen, Francisella tularensis. Early work with a prototype formulation, evaluated for use against the F. tularensis live vaccine strain, showed that a single dose of liposomal ciprofloxacin given by the intranasal or inhalational route could provide protection in a mouse model of pneumonic tularemia. Liposomal ciprofloxacin offered better protection than ciprofloxacin given by the same routes. Liposomal ciprofloxacin has been further developed by Aradigm Corporation for Pseudomonas aeruginosa infections in patients with cystic fibrosis and non-cystic fibrosis bronchiectasis. This advanced development formulation is safe, effective and well tolerated in human clinical trials. Further evaluation of the advanced liposomal ciprofloxacin formulation against the highly virulent F. tularensis Schu S4 strain has shown that aerosolised CFI (Ciprofloxacin encapsulated in liposomes for inhalation) provides significantly better protection than oral ciprofloxacin. Thus, liposomal ciprofloxacin is a promising treatment for tularemia and further research with the aim of enabling licensure under the animal rule is warranted.